Implementasi Penerapan Kaidah Al-Mashaqqah Tajlib Al-Taysir Dalam Praktek Sosial-Ekonomi - Dimyati, Dimyati; Qolbi, Aiunun (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2024)
As a religion that prioritizes the values of public welfare, Islam introduces the principle of al-mashaqqah tajlib al-taysir as a means to address difficulties. This principle, which means that hardship brings ease, applies to nearly all issues related to fiqh (Islamic jurisprudence). It serves to emphasize the verses of the Qur'an and the hadith that highlight how Islam, from its inception, is oriented toward facilitating ease for its followers. One of the reasons a mukallaf (accountable person) experiences ease is the existence of difficulties (mashaqqah). Mashaqqah can stem from actions taken or arise independently of those actions. This raises the question: can all forms of mashaqqah lead to concessions, or only certain types will bring relief to those who experience them? Islam offers many forms of ease, including the reduction of obligations, the prioritization of actions, postponement, and the alteration of responsibilities. This relief applies not only to acts of worship (‘ubudiyah) but also to social and economic practices. The ease granted by Allah SWT should not be interpreted as a trivialization of the religion; rather, it is intended to ensure that mukallafs can fulfill His commands and avoid prohibitions without violating the established rules. A detailed understanding of the concept of rukhsah (concessions) is essential to prevent the development of a dismissive attitude toward the law (mutasahil bi al-ahkam).